Sphingosine Kinase: A Novel Putative Target for the Prevention of Infection-Triggered Preterm Birth - Vibhuti Vyas; Charles R. Ashby; Sandra E. Reznik (Obstetrics and Gynecology International, 2013)
Preterm birth is defined as any delivery before 37 complete weeks of gestation. It is a universal challenge in the field of obstetrics owing to its high rate of mortality, long-term morbidity, associated human suffering and economic burden. In the United States, about 12.18% deliveries in 2009 were preterm, producing an exorbitant cost of $5.8 billion. Infection-associated premature rupture of membranes (PROM) accounts for 40% of extremely preterm births (<28 weeks of gestation). Major research efforts are directed towards improving the understanding of the pathophysiology of preterm birth and ways to prevent or at least postpone delivery. Endothelin-1 (ET-1) is a potent vasoconstrictor that plays a significant role in infection-triggered preterm birth. Its involvement in a number of pathological mechanisms and its elevation in preterm delivered amniotic fluid samples implicate it in preterm birth. Sphingosine kinase (SphK) is a ubiquitous enzyme responsible for the production of sphingosine-1-phosphate (S1P). S1P acts as second messenger in a number of cell proliferation and survival pathways. SphK is found to play a key role in ET-1 mediated myometrial contraction. This review highlights SphK as a prospective target with great potential to prevent preterm birth.